Duolingo: An Alternative Application for Learning English Grammar and Vocabulary - Widodo Widayanto; Ahmad Syafi'i (Journal of English Language Teaching and Islamic Integration, 2020)
This  article  explores  about  the  using  an  already  existing language  learning  app,  Duolingo,  as  an  alternative  application  for learning English grammar and vocabulary. Duolingo is a platform that provide a language-learning website and app. The app and the website are free, so everyone can use it without giving any extra fee. The aim of this  application  is  to  teach  vocabulary  and  grammar,  which  some exercise  series  that  can  be  chosen  by  the  user.  In  this  study,  writer discuss  about  the  using  of  Duolingo  in  mobile  version.  The  writer consider  that  almost  student  in  this  era  are  using  mobile  phone. Hopefully  by  using  this  application,  will  motivate  student  in  learning English, especially grammar and vocabulary.